Memória e sensibilidades: o feminino na literatura da fronteira oeste do Rio Grande do Sul - Soares, Tanira Rodrigues (2014)
The theme we approach in this dissertation is inserted in the research area “Memory, Culture, and Identity” at the Professional Master Course on Social Memory and Cultural Assets, and we aim at studying memory and sensitivity in women’s literature from the western frontier of the state of Rio Grande do Sul, Brazil, more specifically the literary works “Limites” (2002), by Tânia Lopes, and “Baguala” (1982), by Ieda Inda. These works have been chosen due to the approach that has been employed in them, since they are both women’s works that share as background the society in the state’s western frontier, and highlight the role of female characters in their plot. The methodology we have utilized include qualitative, explanatory, and descriptive research, along with documentary and bibliographical research, as well as field research. The theoretical references on memory, literature, and sensitivity are the studies by Pollak (1992), Gondar (2005; 2008), Bosi (1994), Moisés (1997), Tavares (1996), Candido (1967), Lajolo (1983), Dalcastagnè (2005; 2007), Perrone-Moíses (1998), Gruzinski (2007), Leenhardt (2010), Pesavento (2004; 2007), Santos (2008a), among others that support the aim of this work. “Limites” and “Baguala” complement each other as literary representations of this frontier context, two neighbor cities that have frontier with Argentina, taking into consideration individual and collective memory, as well as historical and sociocultural factors. In this sense, this study allows us to access the individual memory of both writers, as well as the collective memory of those living near the western frontier, which reveal peculiar aspects that are highlighted by the writers’ sensitivity. “Limites” and “Baguala” show us women as members of the western human archipelago, where they weave attitude and handle the reins of their own lives. The outcome of the Professional Master Course comprises 8 publications in the Jornal Folha de Itaqui and a Colloquium called “Memória e Sensibilidades na Produção Literária Feminina da Fronteira Oeste do RS”, to be held in Itaqui, Rio Grande do Sul.